Curved running in soccer: kinematic differences between the inside and outside limbs - Brice, P.; Smith, N.; Dyson, R. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
Research on curved running has focussed on track running, using radii not applicable to common movements in many sports. The nature and function of the inside and outside limbs movement remains undocumented in the literature. Common radii of curved runs and typical movement speeds were noted from English Premier League soccer. Eight male soccer players ran at three speeds (3.5 m/s, 4.5 m/s, 5.4 m/s) during straight (0m), and along a curve of radius 3.5m on natural turf. Three dimensional kinematic data was collected using Peak Motus software at 50 Hz. During curved running results indicated reduced range of motion at the outside and inside ankle and knee, but greater hip joint range evident at the inside compared to the outside leg, with emphasis at higher speed. Greater hip flexion positions the centre of mass to allow body lean to complete the curve.